The role and place of foreign languages in Russian culture - Anna V. Pavlovskaya; Oksana A. Ksenzenko (Peoples' Friendship University of Russia (RUDN University), 2022)
Foreign languages have always occupied a prominent place in Russia and the Russian culture. The paper states that despite being seemingly isolated from the outside world, Russia has always been closely connected with it, and not only by trade and political relations, but also by spirit and culture. The research contributes to the discussion of the role of foreign languages in Russian culture and reviews the development of the foreign languages teaching system in Russia. Adoption of Christianity was the first significant reason for the spread of foreign languages in the society, and that brought not only a new religion, but also the Greek language along with the theological books. Over time, more and more foreign languages began to spread in the society, sometimes even entering into conflict with one another: Latin with Greek (in the theological field), German with French (in the sphere of politics), and French with English (in the literary field). In certain historical periods (for example, in the first half of the 19th century), foreign languages even displaced the Russian language in some social strata. The contribution underlines the importance of analysing such historical periods with special reference to the interconnection between language as a means of communication and national identity. The investigation also argues that at times, for example, like in Soviet times, foreign languages acquired the status of 'dead' languages and became an exclusive tribute to tradition and a means of reading. In conclusion, the paper declares that foreign languages have always retained their important role, opening up new horizons for the Russian people and connecting them with the outside world.